Análise das propriedades psicométricas da versão brasileira do inventário “Parcours Amoreux des Jeunes-PAJ” - Campos, Mariana Rocha da Silva (2015)
Introduction: worldwide, is recognized the importance of cross-cultural studies to study comprehensive, multi-faceted and multi-causal phenomena, such as interpersonal violence among young people, considering the impact of the indicators of this research in the exchange of knowledge and actions for the prevention and control of factors risk and vulnerabilities. It is known that this type of research requires the use of validated research instruments in order to ensure its quality and therefore the results obtained after its application in other studies. The analysis of the psychometric properties, reliability and validity of an instrument is critical to ensure that it is calibrated to measure the phenomenon to which it is proposed. Objective: to determine the psychometric properties of the Brazilian version of the inventory "Parcours des Jeunes Amourex" - Loving Trail Youth - PAJ through construct validation and reliability analysis. Methodology: methodological study which deals with the construct validity and reliability (psychometric analyzes) of the Brazilian version of the PAJ, executed in the period 2013-2015, using a convenience sample of 380 adolescents and young adults in the age groups 14-24 years enrolled in public schools in Feira de Santana, Bahia-Brazil. This research represents the second stage of cultural adaptation process and inventory of content validation, carried out from 2011-2013, which led to the national version (adapted and validated). The original inventory and the national version consist of 64 questions in different formats (dichotomous, open, scales). And reliability analysis was used examining the internal consistency of the questions, by calculating the Cronbach's alpha coefficient, considering the satisfactory value> 0.6; the factorability of the questions was evaluated by the test Kaiser-Meyer-Olkin Measure of Sampling Adequacy (KMO), with appropriate value> 0.5; the construct validity was verified through exploratory factor analysis using the principal component analysis technique, with varimax rotation, using the latent root criterion to define the number of factors to be extracted. Results: The data showed that the adapted version of the PAJ has construct validity of evidence, since the measures proposed construct and has adequate reliability coefficients, confirming the internal consistency of the scale. It can be said then that the inventory showed good psychometric parameters allowing its applicability in national studies that seek to investigate violence among young couples and factors related to family life and friends. Conclusions: This research contributes to the appropriateness and applicability of an inventory that assesses multiple dimensions of loving violence in youth, encouraging new studies, exchange of information between different contexts, and can support public policies and programs that lead to the prevention and cure cycle intergenerational victimization and aggression between present and future generations.